Constraints to fertilizer use in Nigeria: Perspectives and insights from the agricultural extension service - Banful, Afua Branoah; Nkonya, Ephraim M.; Oboh, Victor (International Food Policy Research Institute, 2009)
The importance of agriculture in Nigeria's economy cannot be understated. Farming and livestock rearing is the main livelihood for over 70 percent of households in the country. In 2008, agriculture contributed 42 percent of the country's GDP, significantly higher than the 18 percent derived from petroleum and natural gas production. However, the country's promising agricultural potential has not been realized. In all likelihood, low fertilizer use is a major factor in explaining the stagnant agricultural productivity in Nigeria. Widespread introduction of fertilizer began in the late 1970s with the proliferation of Agricultural Development Projects (ADPs). This brief presents the insights of village extension agents (VEAs) who are at the heart of the ADP concept and provide a uniquely informed perspective of the constraints to fertilizer use in the country.